Programs of profit sharing and results - law n. 10.101/2000 and functional comprometimento in bahian fertilizer industries - Marta Maria Santos de Jesus Andrade (2007)
The objective of the present research is to evaluate the relative importance of the Program of Participation in Profits and Results (PPLR) â Law number 10.101, for the commitment of employees in comparison with other factors of functional commitment. Exploratory and descriptive research was conducted, through case studies, with the use of a questionnaire middle structured questionnaire and an interview by topic with managers of PPLR and employees of the administrative, commercial, and operational areas of two large fertilizer companies in Bahia. The research involved two managers and seventy nine employees. The results were analyzed quantitatively and qualitatively. The research allowed to confirm that in spite of the importance of the PPLR for organizational strategies and objectives, there was no agreement between the companies in what it concerns to the prevalence of the Program when related to factors of affective, normative compromising and other calculatives related in the study. It is suggested that several aspects compete for the dissonance among the case studies researched, as the geographical location, demographic subjects and the style of the administration.